Feto-maternal outcome in COVID-19 positive patients with hypertensive disorders in pregnancy - Chavan, Niranjan N.; Mirza, Hera S.; Sonawane, Priyanka; Iqbal, Umme Ammara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Since the first confirmed case in December 2019, the data pertaining to the COVID-19 pandemic has been rapidly evolving. In current study, the relation of COVID-19 and its effect on pregnant women with hypertensive disorders in pregnancy, including symptoms and foetomaternal outcome were studied. Methods: Women with hypertensive disorders in pregnancy consecutively admitted for delivery and tested via nasopharyngeal swab for SARS-CoV-2 using reverse transcriptase polymerase chain reaction (RT-PCR) from 1 April 2020 to 30 September 2020 were included in the study. Results: In our study, 56 women having hypertensive disorders in pregnancy with COVID-19 infections delivering 60 babies (4 twins), 46.43% were in the age group of <25 years, 51.78 % were <37 weeks gestation. Delivery was by caesarean section in 76.78%. Out of these, 33.92% patients required ICU admission. 40% babies delivered had birth weight of <2.5 kg out of which 13.33% had IUGR and 26.66% were preterm. There was 13.33% stillbirth and 6.66% neonatal deaths. 4 maternal death has been reported. Conclusions: With the current data available it does not appear that pregnant women are at increased risk of severe infection than the general population, but clinicians should be aware of high-risk groups. Women will need to be monitored in their booking maternity units and should be transferred to centres with appropriate neonatal intensive care facilities for delivery. In pregnant women with COVID-19 infection, if maternal illness is not severe, the considerations should be based more on obstetric indications for delivery.